Durability Performance of Palm Oil Fuel Ash Cement Based Aerated Concrete in Marine Environment - Khairunisa, Muthusamy; Mohd Warid, Hussin (2011)
The ever popular issue on environmental preservation and sustainability all over the world has lead towards the innovation of new materials from either industrial or agricultural waste. Malaysia being one of the leading producers of palm oil has been conducting numerous researches to discover the various potentials of by-products generated by palm oil mills. The current findings revealed that palm oil fuel ash (POFA) produced in the mills can be used for producing a new alternative lightweight construction material known as POFA cement based aerated concrete having enhanced strength than specimen produced using 100% ordinary Portland cement. Since, the performance this material in marine environment is unknown, this paper presents and discusses the result on the strength performance of this lightweight concrete upon exposure to sea water for one year. The concrete cubes were prepared and subjected to water curing for 28 days before immersed in sea water. The compressive and flexural strengths of the specimens were tested at 3, 6 and 12 month following the procedures stated in BS 1881: Part 116 and ASTM C293-79 respectively. The study found that integration of POFA as partial cement replacement in aerated concrete enhances the performance of concrete in sea water environment.